Serum extracellular matrix biomarkers in rheumatoid arthritis, psoriatic arthritis and psoriasis and their association with hand function - Port, Helena; Coppers, Birte; Tragl, Sonja; Manger, Eva; Niemiec, Lisa Maria; Bayat, Sara; Simon, David; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne Christine; Tascilar, Koray; Hueber, Axel; et al. (Scientific Reports, 2025)
Inflammatory arthritis, including rheumatoid arthritis and psoriatic arthritis, is characterized by physical function impairment. This becomes apparent even before arthritis onset, as in psoriasis (PsO). Chronic inflammation triggers an accelerated remodeling of the extracellular matrix (ECM), resulting in released ECM fragments detectable in blood. We aimed to investigate levels of blood-based ECM biomarkers in patients with RA, PsA, PsO, and healthy controls and to explore the association of ECM biomarkers with hand function impairments. Patients with RA (n = 85), PsA (n = 115), PsO (n = 102) and controls (n = 110) were included in this cross-sectional study. ECM catabolic (C1M, C2M, C3M, C4M, PRO-C4, C6M, ARG), formation (PRO-C1, PRO-C3, PRO-C6) and inflammation biomarkers (VICM) were measured in serum from all patients. Objective hand function (fine motor skills (Moberg-Picking-Up Test), isometric grip strength (dynamometer) and patient-perceived hand function (Michigan Hand Questionnaire (MHQ)) were assessed. Patients with RA and PsA received treatment with disease-modifying anti-rheumatic drugs. VICM levels were higher in RA, PsA, and PsO than in controls (p < 0.0001). PsA and PsO showed higher C4M levels compared to controls (p < 0.0001, p < 0.0001), while C6M was lower in patients with RA, PsA and PsO than in controls (p < 0.0001, p < 0.001, p < 0.01). PsO presented with higher levels of C1M compared to controls and to RA (p < 0.001 and p < 0.0001). PRO-C6 correlated negatively with MHQ (ρ = -0.39, p < 0.01) and grip strength (ρ = -0.31, p < 0.05) in PsO, while only weak correlations were observed between biomarkers and hand function scores for RA and PsA patients (all ρ < ± 0.2–0.3). Patients with RA, PsA, and PsO showed significant alterations in ECM remodeling biomarkers. Especially PsA and PsO had higher levels of inflammatory biomarkers compared to RA and controls, likely due to modulation by treatment. Predominantly in PsO, ECM formation biomarkers were associated with hand function impairments.<br
Keywords: Extracellular matrix; Biochemical markers; Rheumatoid arthritis; Psoriatic arthritis; Psoriasis; Hand function

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ACR Open Rheumatology, 2020)
ObjectiveThe objective of this study was to compare the impact of psoriatic disease (psoriatic arthritis [PsA] and psoriasis) and rheumatoid arthritis (RA) on objective and subjective parameters of hand function.
CRIS-Team WoS Importer:2021-07-16

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

SUBJECTIVE ASSESSMENT OF PHYSICAL FUNCTION DOES NOT SUFFICIENTLY EXPLAIN VARIANCE OF MEASURED HAND FUNCTION AND GRIP STRENGTH IN ARTHRITIS PATIENTS AND NON-ARTHRITIS CONTROLS - Liphardt, Anna-Maria; Tascilar, Koray; Coppers, Birte; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Bayat, Sara; Simon, David; Sticherling, Michael; Rech, Jürgen; Hueber, A.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04